Sebuah SOSIALISASI PERNIKAHAN DINI PADA MASYARAKAT DESA PANDANSARI KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Zamzami, Ahmad Haikal Zamzami; Khoir, Akiful; Febriyanti, Alifia Putri; Mufarrichah, Binti Ni'matul; Aini, Dewi Nur; Ningrum, Diva Libriyani Syauqi; Zahrah, Nada Nafisati (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2023)
Based on research and interviews, there are 16 people consisting of 1 man and 15 women who get married at the age of 19 in 2022 from January to December. Health impacts both psychologically and biologically often occur for couples who are not physically or mentally prepared. This can be in the form of child mental health disorders, domestic violence, malnutrition, premature babies, physical disabilities, or even death in the mother and fetus and child. Early marriage is usually motivated by social matters such as economic problems, traditions, getting pregnant outside of marriage, low levels of education , and coercion from the old man himself. One of the efforts to reduce cases of early marriage has been carried out quite often by the Pandansari Village government in collaboration with the Poncokusumo District KUA and the Poncokusumo District HEALTH CENTER namely carrying out socialization to all levels of society in Pandansari Village. In Indonesia, the minimum age for a person to perform marriage is at the age of 19 years as stated in Article 7 of the Marriage Law No. 16 of 2019 . In Islam itself, the law of marriage is mubah or permissible, but it can change its law according to one's wishes or wishes . In carrying out the marriage of the bride and groom and their families, they must pay attention to the legal aspects of the marriage so as not to cause chaos in the future , especially in baligh age for the bride and groom.